Physiological Role and Use of Thyroid Hormone Metabolites - Potential Utility in COVID-19 Patients - Fröhlich, Eleonore; Wahl, Richard (Frontiers in Endocrinology, 2021)
Thyroxine and triiodothyronine (T3) are classical thyroid hormones and with relatively well-understood actions. In contrast, the physiological role of thyroid hormone metabolites, also circulating in the blood, is less well characterized. These molecules, namely, reverse triiodothyronine, 3,5-diiodothyronine, 3-iodothyronamine, tetraiodoacetic acid and triiodoacetic acid, mediate both agonistic (thyromimetic) and antagonistic actions additional to the effects of the classical thyroid hormones. Here, we provide an overview of the main factors influencing thyroid hormone action, and then go on to describe the main effects of the metabolites and their potential use in medicine. It appears that i) the more potently-acting molecules T3 and triiodoacetic acid have shorter half-lives than the less potent antagonists 3-iodothyronamine and tetraiodoacetic acid; ii) reverse T3 and 3,5-diiodothyronine may serve as indicators for metabolic dysregulation and disease, and iii) Nanotetrac may be a promising candidate for treating cancer, and resmetirom and VK2809 for steatohepatitis. Further, intravenous infusion of T3 may find application in the treatment of critically ill patients with Severe Acute Respiratory Syndrome-CoronaVirus-2 (SARS-CoV-2) pulmonary infections.